Modality effects in language switching: Evidence for a bimodal advantage - KAUFMANN, EMILY; MITTELBERG, IRENE; KOCH, IRING; PHILIPP, ANDREA M. (Bilingualism (Cambridge, England), 2018)
In language switching, it is assumed that in order to produce a response in one language, the other language must be inhibited. In unimodal (spoken-spoken) language switching, the fact that the languages share the same primary output channel (the mouth) means that only one language can be produced at a time. In bimodal (spoken-signed) language switching, however, it is possible to produce both languages simultaneously. In our study, we examined modality effects in language switching using multilingual subjects (speaking German, English, and German Sign Language). Focusing on German vocal responses, since they are directly compatible across conditions, we found shorter reaction times, lower error rates, and smaller switch costs in bimodal vs. unimodal switching. This result suggests that there are different inhibitory mechanisms at work in unimodal and bimodal language switching. We propose that lexical inhibition is involved in unimodal switching, whereas output channel inhibition is involved in bimodal switching.